Dual beam and dual circular polarized multiplexing reflectarray for Ku band satellite communication - Yutian Ma; Yuhui Ren; Lehu Wen; Rongli Zhao; Ke Li; Fuwei Wang; Feng Cui; Handong Wu (Scientific Reports)
Abstract In this letter, a broadband low-profile dual circularly polarized reflectarray (dual-CP RA) for Ku-band satellite communications is proposed. A novel single-layer metasurface unit cell consisting of a functional layer, an air layer and a metal plate is investigated first. The functional layer is a metal structure printed on the F4B substrate. The air layer can effectively extend the bandwidth, and the overall profile is only 0.12λ 0, where λ 0 represents the wavelength at 11.725 GHz. To independently control the phase of left-handed circularly polarized (LHCP) and right-handed circularly polarized (RHCP) waves, Dynamic phase and Berry phase methods are employed by either changing the size of microstrip lines or the rotating of the cells. Finally, a dual-CP RA with 1600 cells is designed to realize two beams at 20° for LHCP wave and − 20° for RHCP wave at 11.725 GHz. The measured gain for LHCP wave is 29.1 dB with the aperture efficiency (AE) of 47% and 1-dB gain bandwidth of 37.4%, while the gain, AE, and bandwidth for RHCP wave are 29.22 dB, 48.3% and 37% respectively.